Tuberculosis Testis In Middle-Aged Male As A Rare Case Of Genitourinary Tuberculosis: A Case Report: Tuberkulosis Testis Pada Pria Dewasa Muda Sebagai Kasus Langka Tuberkulosis Genitourinari: Laporan Studi Kasus - Surya, Prima Ardiansah; Faadilah, Ashifa Hasna; Indarjadi, Ignasius; Wirjopranoto, Soetojo; Jamhari, Muhammad Arif Hakim; Azmi, Yufi Aulia (Medicra (Journal of Medical Laboratory Science/Technology), 2023)
Introduction: Testicular tuberculosis is a very rare type of urogenital TB. Case Presentation: A 36 year old man came to the emergency room because of pain in the right testicle accompanied by swelling and discharge. Orchiectomy on the dextra testis was continued with treatment using category 1 OAT for 9 months after the diagnosis was made using anatomic pathology examination. Discussion: The physical examination needs to be done carefully because most general practitioners consider testicular enlargement to be a malignancy. Urogenital tuberculosis requires 6 months of treatment and 9 months of treatment in patients with certain conditions. Conclusion: Prompt and precise diagnosis if testicular TB is necesssary to prevent infertility, the most common complication